Application of Criminal Sanctions for Perpetrators of Tax Crimes (Case Study of Case Decision Number: 213/Pid.Sus/2021/PN.Jkt.Brt) - Manullang, Jus Marsondang; Prastyanti, Rina Arum; Hastuti, Indra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to find out and describe the mechanism for resolving the application of sanctions for tax crime perpetrators and the consideration of the Panel of Judges in applying criminal sanctions to tax crime perpetrators as stated in Case Decision Number: 213/Pid.Sus/2021/PN.Jkt.Brt where the Panel of Judges imposes a prison sentence of 2 (two) years and 6 (six) months, which is lower than 9 (nine) months compared to the Public Prosecutor's demands. The type of data in this study is secondary data. The data collection technique uses the library search method, which is to systematically study and analyze laws and regulations, books, magazines, newspapers, materials from the internet and other materials related to the object of research, namely tax crimes. Based on the results of research on tax crime cases at the West Jakarta District Court with Decision number: 213/Pid.Sus/2021/PN.Jkt.Brt with the Defendant Bambang Purwosetiyo, Judge's Consideration Based on the Testimony of Witnesses, Evidence, Public Prosecutor's Indictment and Public Prosecutor's Demands. Based on these considerations, the Judge stated that the Defendant must be declared to have been legally and convincingly proven to have committed a criminal act. In addition, during the examination at the trial, the Judge did not see that the Defendant was suffering from an illness, the Defendant was able to answer well and smoothly the questions posed to him, both by the Panel of Judges, the Public Prosecutor, thereby strengthening the opinion and confidence for the Panel of Judges that the Defendant is able to be responsible according to criminal law for the acts he committed. The judge decided to impose a prison sentence of 2 (two) years and 6 (six) months and a fine 2 x 2 X Rp. 4,761,272,973,- (one billion two hundred and seventy-four million six hundred and fifteen thousand eight hundred and twenty-one rupiah). = Rp.9,522,545,946,- (Nine billion five hundred and twenty-two millionfive hundred and forty-five thousand nine hundred and seventy-three rupiah), while the Public Prosecutor demanded a prison sentence of 3 (three) years and 3 (three) months and a fine of 2 X Rp. 4,761,272,973,- (one billion two hundred and seventy-four million six hundred and fifteen thousand eight hundred and twenty-one rupiah). = Rp.9,522,545,946,- (Nine billion five hundred and twenty-two millionfive hundred and forty-five thousand nine hundred and seventy-three rupiah), thus the Judge's decision is 9 (nine) months lower than the Public Prosecutor's demand. There is no detailed explanation regarding the Judge's consideration in deciding on a prison sentence that is 9 (nine) months lower than the Public Prosecutor's demand.